Nail lesions in red squamous lichen planus: a review of the literature - R. V. Saranyk; T. A. Gosteva (Лечащий Врач, 2024)
Background. Lichen planus is a chronic inflammatory disease affecting the mucous membranes, skin and its appendages. Nail lesions in lichen planus are quite common, which leads to a negative psychological and physical impact on patients. In addition to nail lesions against the background of the underlying disease, there are also isolated forms in which only the nail plates are affected in patients with lichen planus without involving the skin and mucous membranes. Changes in the nail plates in lichen planus can be irreversible, destroying the nail plate itself and the entire nail apparatus.Objective. The aim of this article was to study the most common nail lesions in lichen planus.Materials and methods. In the period from April to July 2024, we analyzed publications from the PubMed and eLibrary databases devoted to nail lesions in lichen planus. The search queries included "Nail lichen planus", "Lichen planus", "Nail lichen planus", "Trachionychia", "Twenty nail dystrophy", "Dermoscopy nail lichen planus".Results. The study revealed that the most common nail lesions in lichen planus are longitudinal grooves, general dystrophic changes in the nails in the form of their fragility, onychorrhexis and trachyonychia. It was also noted that lichen planus is characterized by severe irreversible changes in the nails, such as anonychia and pterygium. In the course of this work, we noted the evolution of pathological changes in the nails in lichen planus. This observation can be useful in the diagnostic search and choice of treatment tactics in the early stages of the lesion.Conclusion. Timely diagnosis of pathological changes in the nails in lichen planus is crucial in choosing patient management tactics. The development of irreversible lesions of the nail plates in lichen planus should be prevented by treating earlier pathological changes.